KAJIAN EVALUASI PEMANFAATAN DANA BANTUAN HIBAH DAN BANTUAN SOSIAL KOTA TARAKAN - Midiansyah Midiansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The purpose of the study was to identify and determine : (1) the amount of fund allocation , the total value , kind and type of aid that has been disbursed, kind and type of target groups that have received assistance through the Grant Assistance Fund and Social Assistance in Tarakan, (2) common problems and rise’s obstacles, (3) the factors that drives the implementation of activities / programs, (4) community activities / programs : (5) the succession  level of the allocation use, and (6) develop management strategies that effective and efficient to use Grant Aid Allocation and Social Assistance in the City of Tarakan. The experiment was conducted from March to August 2011 in Tarakan. This research study took place in 4 (four) districts in Tarakan include East Tarakan, Middle Tarakan, West and North Tarakan districts,  which has been getting running Allocation.Preparatory activities undertaken to complete the initial phase of the administration and coordination of inter-agency cooperation, an inventory of the tools and materials are needed, stabilization of work’s programs, observation, collection data and analysis data. Primary data were obtained through direct observation and interviews with sources and secondary data obtained from various departments /agencies in the form of literature, study reports and annual reports are relevant to the study.Compilation of data is the selection of the data and information obtained are then grouped according to the analysis needs to be performed. After the compilation stage is done, followed by a descriptive analysis and interpretation of the results carried out the analysis. In addition, decision-making is done by using the scoring.The results showed that :1.    The amount of budget that allocated for Grants and Bansos Tarakan City in year 2010 is Rp.185.420.879.657,84 with the realization of the budget that can be absorbed by Rp. 152.,384.512.199,84 , - or 82.18 %, and the rest of the budget that is not absorbed is Rp. 33.036.367.158,00, - or a total of 17.82 % from the total budget. The budget allocation is used to buying subsidies at Local Company (Perusda); Allocation of Funds for the Central Government Institutions (Vertical) in Regional, Allocation of Funds for Agency / Private Organizations ; Budget Allocation for Community Group / Individual; Budget Allocation for Social Assistance Organization; The allocation of political party assistance; Unexpected Expenditure allocation and allocation of Local Government Finance.2.    Target groups that obtain grants and Bansos funds : Vertical existing institutions in the Region; Agency/Institution/Organization Private; Community Group/Individual; Social Organization; Help Political Party (political party); Variable Expenses.3.    Factors to be problems and obstacles are : (a) the funds are not fully absorbed by the public, (b) the administration’s proposal is still considered as too complicated; (c) Human Resources of respondents still relatively limited, and (d) regulations/guidelines are always changing; (e) technically planning’s activities program does not exist and the location of the development is not clear/overlapping/related legal issues; (f) expenditure accounts often do not conform with the RKB/RAB proposal; (g) disappointment and a sense of not community is proud of the distribution of funds is still high; (h) the provision of grants and Bansos are not in accordance with procedure, generally have not been given strict sanctions and (j) the report’s indication made by organizations or community groups and individuals are fictional.4.    Factors that drives the implementation and management of Social Aid Grants, that are : (a) trend and Social Aid Grant Aid for 3 (three) years continues to increase, (b) Grant funds and Bansos still very much needed by the community respondents, (c) City community level is still high vulnerability, especially to cope with emergencies and unexpected disasters, (d) a reference priority measures management has become a common awareness of the Grants and Bansos, in order to build community self-reliance.5.    The level of public perception of the management of grant funds and Bansos in each district following as North Tarakan 71.21% and East Tarakan 71.30%, Central Tarakan 79.17% and West Tarakan 68.33%. Indicators of public perceptions of respondents towards the management of grants and Bansos by 72.34% classified as optimal and only 27.66% classified as not optimal.6.    The level of achievement of the successful management of grant funds and Bansos, obtained the total benefit of the achievement indicators in each of the districts are : North Tarakan 53.05%, East Tarakan 51.91%, Central Tarakan 67.66% and West Tarakan 54.33%. Indicators of the achievement of the total benefit of 56.97% classified as optimal and only 43.03% classified as not optimal.